Optimization of rice, soybean, and yellow sweet potato flour concentrations for improved nutritional and sensory quality of infant food - Abilgos-Ramos, Riza G.; Rizzo, El Shaira A.; Fuentes, Xenia Portia S.; Morales, Amelia V.; Rodriguez, Raffy B. (2020)
Complementary food is important in the first two years of an infant?s life for optimum growth and development. In the Philippines, especially in areas without access to adequate food sources, infants are fed with complementary foods of low nutrient density. To improve the nutrition in areas where malnutrition among 0?2-yr-old children is highly prevalent, this study developed a plant-based complementary food premix from rice, soybean, and yellow sweet potato for infants aged 6?23 mo. Ten (10) complementary food premixes were formulated and optimized using D-optimal mixture design. Results showed that different proportions of flour blends had significant (p < 0.05) effects on protein, ash, fat, carbohydrates, water absorption index, swelling power, and consistency. The optimized complementary food formulation was with the ratio of 50% rice, 35% soybean, and 15% yellow sweet potato flours. A 100-g serving of the complementary food provides 408.77 kcal and 15.68 g of protein.